Histopathological Study and Expression of CD 117 in Renal Cell Carcinoma - Unnikrishnan, Rasmi; I, Praseeda; Sadashivan, Santha (Annals of Pathology and Laboratory Medicine, 2019)
Background: Hypernephroma or Renal Cell Carcinoma (RCC) accounts for over 90% of all malignancies of the kidney occurring in adults. Of all renal cell carcinomas, Clear cell carcinoma accounts for around two-thirds to three-quarters and Chromophobe RCC accounts for around 5%. The present study highlights the diagnostic usefulness of CD117 as a phenotypic marker in Renal Cell Carcinoma. Methods: Current study include 48 cases of histopathology proven renal cell carcinoma. Each case was reviewed and classified according to the WHO classification criteria. The expression of CD117 was assessed using immunohistochemistry. Result: Of the 48 cases studied, 6cases, that is 2 case of Papillary RCC and 3 case of Chromophobe RCC showed moderate intensity and diffuse positivity for CD 117 and 1case of clear cell RCC with sarcomatoid areas showed mild and focal positivity. Papillary RCC showed both cytoplasmic and membrane positivity, while Chromophobe RCC showed mainly membranous positivity. Sarcomatoid areas showed weak cytoplasmic positivity. Conclusion: Histopathology supported by immunohistochemistry is a helpful tool in subtyping the various RCC. Treatment options in advanced disease is minimal. CD 117 positivity may favour the use of targeted therapy in renal cell carcinomas.